A workflow to assess the efficacy of brine extraction for managing injection-induced seismicity potential using data from a CO2 injection site near Decatur, Illinois. (July 2021) - Babarinde, Oladipupo; Okwen, Roland; Frailey, Scott; Yang, Fang; Whittaker, Steven; Sweet, Dustin
Highlights: A workflow is developed to assess the efficacy of brine extraction for managing injection-induced seismicity. Coulomb failure function is used to constrain allowable pressure and determine maximum injection rates that will not induce seismicity. The efficacy of brine extraction to manage injection-induced seismicity is dependent on brine extraction plans. Workflow provides insights on natural fracture distribution in the PCB at the CO2 injection site near Decatur, Illinois. Brine extraction can be used to increase injection rates and concurrently manage potential for seismicity. Abstract: Injection of CO2 for storage in a geologic formation increases pore pressure and alters in situ stresses. Depending on the orientation of any existing fault and fracture planes, such as critically stressed planes, this stress alteration will modify normal stresses acting on planes and could result in frictional sliding and release stored energy in the form of seismicity. Brine extraction (BE) is a technique that can be applied prior to, or during, CO2 injection to reduce pore pressure for increasing storage capacity and, potentially, for reducing the likelihood of frictional sliding. A workflow is described to assess the efficacy of BE for mitigating frictional sliding (i.e., seismicity) during injection and entails: site characterization, stress calculations and failure assessment, static and dynamic modeling, and BE operational planning. Site characterization describes the stress field used to calculate the Coulomb Failure Function (CFF) that constrains allowable pore pressure changes and injection rates in the numerical simulation of CO2 injection scenarios. The inclusion of BE in the workflow allows for determination of the potential need for pressure reduction, and evaluation of the effectiveness of this operation. Example application of the workflow using an injection field dataset near Decatur, IL, provides insight on fracture planes and stresses at the site, formation properties and the impact of variable CO2 injection-rate targets on whether BE plans are required. The study workflow indicates that BE could enhance CO2 injection rate by 39% and correspondingly reduce the potential for injection-induced seismicity as indicated by a reduction in CFF.